Efficacy, Agency and Behavioural Change: Evaluation of a Local/Global Sustainability Education Program - Buchanan, John (Richtmann Publishing, 2012)
As world population increases, and as more and more individuals make increasing demands on the earth’sresources, the mandate for effective Sustainability Education (SE) becomes more urgent. This paperdescribes a longitudinal evaluation of a project currently being undertaken in government primary andsecondary schools in New South Wales, Australia, funded by the NSW Department of Education andCommunities (DEC). The Climate Clever Energy Savers (CCES) Project is designed to raise awarenessamong school students about ways of reducing electricity consumption at their schools. Students areinvited to tender for funds of up to 2000.00 to support a program (such as an education campaign, orbuilding or appliance modification) to reduce electricity consumption. The overarching research questionconcerns the extent to which and ways in which the program has achieved the desired behaviour changesand educational outcomes. We have found the project to be highly effective, but also suggest somemodifications to further enhance its effectiveness.